Influence of an active treatment on quality of life, pain and depression in women with fibromyalgia: a review article - Oliva-Estupiñan, Vildane Felipe (2024)
Fibromyalgia is a syndrome that causes generalized and diffuse muscle pain accompanied by fatigue, although other symptoms also appear, such as depression, anxiety, sleep and rest disturbances, allodynia, and cognitive, psychological and social problems. These symptoms notably affect the patients' quality of life. The forms of presentation of the pathology increase the difficulty of diagnosis and treatment for professionals who treat these patients, with a significant prevalence ratio of 21:1 in favor of women over men. On the other hand, this disease entails a high economic cost, as 2/3 of the expenses are not directly invested to treat the pathology; therefore, they are considered losses. The objective of this review is to demonstrate the effectiveness of adding various active treatments, compared to the usual pharmacological treatment, in improving quality of life and reducing pain and depression in women with fibromyalgia. For this purpose, the WOS, Cochrane Library and PubMed databases were used. Seven articles were selected, aimed at analyzing the effectiveness and safety of therapeutic exercise, a highly cost-effective tool, as part of the treatment of women with fibromyalgia. Clinical trials were selected with at least one intervention group that performed some type of physical activity. The articles indicated that physical exercise as an additional therapy provided benefits in quality of life, pain relief and reduction of depression in women with fibromyalgia compared to those groups that simply followed the usual treatment. Therefore, we can conclude that the usual (drug-based) treatment, accompanied by an active treatment, offers greater benefits in the three abovementioned aspects when compared to treatment with drugs alone. Active treatment is considered safe to add to our toolbox for treating the symptoms of fibromyalgia. Depending on the patient's symptoms, tastes and preferences, we could recommend or prescribe different types of physical activity to promote adherence and tailor the treatment for each case.